(untitled) (Journal of the College of Education for Women, 2019)
Stop and stop Alsergsti classed many of the characteristics of great poets andliterary arts and persuasions, in Mqamth cash cash Antzmtha three criteria: thestandard of Islam and the standard time, and Maaartadd purposes of poetry. Thishas had its effect on lighting stand many of the goals of the poets and theirattitudes.The first criterion: Those who study the positions of Alsergsti to poetry andpoets must be discerned his money comes from the spirit of Islam as a religion andcreed and a system, a position that is encouraging him wherever expressed, such asthe Muslim community the new values, away from the vulgarity, which contributedto the formulation of the standard of religious poetry criticism.He left the standard of religious Basmath and stir in some of the provisionscash Sergsti in Mqamth addressed by the hair and poets, Fodahm in the ranks of thehouses as Ahtute their poetry or their behavior Nfhat religious and moral values,through brief references devoid of reasoning or depth cash.The second criterion: touch Alsergsti in His criteria of this development thathas plagued templates poetry and its meaning is no longer on the format and theone due to the development of society, emerged as new templates in the Abbasidperiod and the abandonment of many of the templates that I knew in the era of pre-Islam and shortly thereafter, leaving the words many were common before that,leaving her place in the era of civilization and intellectual development andintroduced new meanings and accompanied by the poets Maged in their lives andwhat there was of culture, science and philosophy, but this is not the criticequitable, which gives everyone his due, preferred the old and the neighbor to talk.The third criterion: It is blessed with consideration of the positions Alsergsticash and his art in the standard purposes of poetry finds it has issued for a soundunderstanding of the function of poetry, nature and essence, comes to him fromEkov a long practice of poetry and his studies, and to surround and wide the newsof poets and their curricula and their environments, and the circumstances in whichthey lived, succeeded where including the attributes of artistic talent and sense ofliterary styles slender to absorb the poets and their ways of speech and expressionin Menahihm imaging, and the familiar characteristics and technical features that distinguish them from each other. Although our observations and our reservationsthat we expressed in the body of the standard on some of his views of cash, butAlsergsti as including Ottey of taste and science of hair and the practice of it, to goout to the preference of poets according Migda of quality in Nteghm and themultiplicity of their purposes, an arbitrator taste literary as favored by the productof the poets who Aordam And criticism Alsergsti in Mqamth This is an extensionof the spirit that Vgahnaha in the era before Islam and beyond in terms ofaccreditation in cash on the intuitive, printing and taste the Arab pure, we get all ofthis to the rule of Aasana undeniable: it is the criticism when Alsergsti not rid ofthe old was not liberated of the assets, known before, in terms of taste hair, and itsmeanings and purposes of the trade-off between the poets, Criticism has the self asa whole.We were able to touch all of this without a permit directly from the Alsergstiand we calculated that the literary critic depends terms of the means of his skill andpersonal intuition to capture the significance of the word in the text or a phrase,which we ask Allah that we have been successful in it, and it says payment andreconciliation.